2010
DOI: 10.1007/s10040-010-0592-2
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction between groundwater, the hyporheic zone and a Chalk stream: a case study from the River Lambourn, UK

Abstract: Understanding the processes controlling groundwater-surface water interaction is essential for effective resource management and for protecting sensitive ecosystems. Through intensive monitoring of Chalk groundwater, surface water, and shallow gravel groundwater along a river bank and below the river, using a combination of hydrochemical and hydrophysical techniques a complex pattern of interactions has been elucidated. The river is broadly in hydraulic contact with the river bed and adjacent gravels and sands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Allen et al 2010;Banzhaf et al 2013;Boulton et al 1998;Krause et al 2009). Much less research has been carried out at the local or flood plain scale (Langhoff et al 2006, see also section 2.1.2).…”
Section: Coverage Of Groundwater-surface Water Interaction At the Regmentioning
confidence: 99%
“…Allen et al 2010;Banzhaf et al 2013;Boulton et al 1998;Krause et al 2009). Much less research has been carried out at the local or flood plain scale (Langhoff et al 2006, see also section 2.1.2).…”
Section: Coverage Of Groundwater-surface Water Interaction At the Regmentioning
confidence: 99%
“…This site is approximately 14 km from the ephemeral source of the River Lambourn and encompasses approximately 600 m of river and 10 ha of wetland. The Chalk bedrock at the observatory is overlain by river terrace deposits, which nearby have been demonstrated to comprise primarily coarse-grained gravels that are typically 3-4 m thick (Allen et al, 2010). These are in turn overlain by an assortment of alluvial deposits consisting of peat, clay, silt, sand and gravel.…”
Section: Study Areamentioning
confidence: 99%
“…A number of studies have found that natural attenuation at the groundwater-surface water interface is a significant control on observed river nitrate concentrations (Allen et al, 2010;Lapworth et al, 2011;Pretty et al, 2006;Smith et al, 2009). Lapworth et al (2011) showed that ecologically significant P concentrations (20-30 μg/L) are present in the hyporheic zone in dissolved and colloidal forms.…”
Section: Nitrogen Fate and Transport In Groundwatermentioning
confidence: 99%